Reverse and Forward Translational Neuropharmacology in Psychiatric Drug Discovery. Issue 2 (27th October 2017) - Shaffer, Christopher L.
Abstract : The probability of achieving marketing approval of a novel therapeutic for psychiatric indications is extremely low due largely to the inability to demonstrate durable and reproducible efficacy in phase II trials and beyond. These failures are often attributed to the lack of translation of the underlying neuropharmacology from animal model(s) to the disease population. However, how assured is such a conclusion considering the clinical efficacy path rarely meticulously parallels the preclinical experiment(s) that underwrote it?